2009
DOI: 10.1051/0004-6361/200913161
|View full text |Cite
|
Sign up to set email alerts
|

A ~4.6 h quasi-periodic oscillation in the BL Lacertae PKS 2155-304?

Abstract: We report a possible detection of an ∼4.6-h quasi-periodic oscillation (QPO) in the 0.3-10 keV emission of the high-energy peaked blazar PKS 2155−304 from a 64 ks observation by the XMM-Newton EPIC/pn detector. We identify a total modulation of ∼5% in the light curve and confirm that nominal period by periodogram, structure function, and wavelet analyses. The limited light curve duration allows the capture of only 3.8 cycles of this oscillation and thus precludes a very strong claim for this QPO, despite a nom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 44 publications
(70 reference statements)
5
91
2
Order By: Relevance
“…6)? And indeed in most blazars QPOs have not been detected, but in few QPO was found (Lachowicz et al 2009). This issue need further in- vestigation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…6)? And indeed in most blazars QPOs have not been detected, but in few QPO was found (Lachowicz et al 2009). This issue need further in- vestigation.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Another case of QPO reported in the literature is the blazar PKS 2155-304. Lachowicz et al (2009) reported a 4.6 h QPO in the 0.3−10 keV data (from ObsID 158961401). We have analyzed 8 observations of this source, including this one; none showed indications of a QPO.…”
Section: Qpo Detectionmentioning
confidence: 99%
“…Groth 1975;Deeter & Boynton 1982;Israel & Stella 1996;Vaughan 2005). When determining the significance of possible periodicities in the PSD, the red-noise has to be accounted for in order not to severely overestimate the significance of identified frequencies (Lachowicz et al 2009). In this paper, we account for the red-noise properties when performing a periodogram analysis.…”
Section: Introductionmentioning
confidence: 99%